Cyclic behavior of damage-controllable steel fiber reinforced high-strength concrete reduced-scale frame structures. (1st April 2021) - Liu, Juan; Zhang, Jianwei; Li, Xiangyu; Cao, Wanlin
Highlights: The cyclic behavior of steel fiber reinforced high-strength concrete frame structures with high-strength steel rebars was investigated. All frames successfully achieved the secondary stiffness. Incorporating ultra-high-strength rebars in frame columns could make the inter-story displacement distribution relatively uniform. An ideal load-deformation behavior of the damage-controllable frame was proposed. Abstract: To obtain desirable damage-controllable frame structures, three 1/3-scale, 2-bay, 2-story steel fiber reinforced high-strength concrete frames with high-strength steel rebars were fabricated and tested under combined axial load and cyclic lateral load. Under the principle of equal strength design, three types of columns with different arrangements of longitudinal rebars were designed (i.e., the first only reinforced with HRB 600 MPa high-strength steel rebars, the second reinforced with hybrid HRB 600 MPa high-strength and 1200 MPa ultra-high-strength (UHS) steel rebars, and the third only reinforced with UHS steel rebars), while the beams were generally reinforced with HRB 600 MPa steel bars. The test results reveal that all frames exhibited comparative seismic performance and represented acceptable residual deformation before a lateral drift of 3%, which can be a promising alternative to traditional frames. Incorporating UHS rebars in frame columns could make the inter-story displacement distribution relatively uniform, which would avoid the damage concentration in the bottom floor and the collapse of the structure. Compared to the frame merely with HRB 600 MPa rebars in the column, the frames with UHS rebars showed a positive lateral stiffness in a considerable deformation range after the formation of the plastic hinge in the beam, and the residual displacement and residual crack width were effectively controlled. The proposed ideal load-deformation behavior of the damage-controllable frame can clearly reflect the failure mechanism of the structure, and the secondary stiffness ratios of different stages can be obtained to accurately evaluate the damage control performance of the structure at different stages.